Analysis of Timor’s Hyptis suaveolens L Poit Leaves - Mali, Ferdianus; Wogo, Hermania Em; Lerrick, Reinner Ishaq (Chemistry Notes, 2020)
Analysis of essential oil contained in Timor Hyptis suaveolens L Poit leaves has been done over GC-MS spectrometer. By distilling of the pre-dried leave samples using Stahl apparatus, there was 0,134% colored yellow and typical oil yielded. The GC-MS detected 33 compounds mainly 16,47% of trans-caryophillene, 16,09% of 1,8-cineole, 8,32% of caryophyllene oxide, 6,67% of 3 cyclohexene-1ol,4-methyl-1-1 and 2,7,6,24% of 11-cyclotetradecatrien-1-ol. Moreover phenol-2-methoxy trans-caryopillene, a-gurjunne, phenol-2,4-bis, 1-hexadecene, a-cedrol and cembrene have been found as new chemotype in comparison to 10 suoveolens from different countries, planting condition and/or climates.